LEVERAGING ARTIFICIAL INTELLIGENCE FOR ELT: A SYSTEMATIC REVIEW - Naila, Najmi; Hajija, Iis; Torihoran, Naf'an (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
Artificial Intelligence (AI) in English language learning (ELT) is growing rapidly, offering personalized learning, instant feedback, and better student engagement. However, Challenges include usage ethics, technology dependence, and educator readiness. Prior research on AI's advantages and difficulties in ELT is summarized here. A systematic review using the PRISMA method analyzed 15 studies from various academic sources related to AI in English language learning, such as PubMed, ScienceDirect, Taylor & Francis, and Mendeley. AI has been found to improve students' language skills, motivation, and engagement through tools such as chatbots and machine learning. However, challenges such as plagiarism, lack of long-term studies, and educator readiness still need to be addressed. AI has the potential to improve ELT, but it requires a mature implementation strategy to address ethical challenges, teacher training, and long-term effectiveness. Keywords: AI in Education, Artificial Intelligence, English Language Teaching, Systematic Review.